2021
DOI: 10.1007/s00204-021-03164-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell survival after DNA damage in the comet assay

Abstract: The comet assay is widely used in basic research, genotoxicity testing, and human biomonitoring. However, interpretation of the comet assay data might benefit from a better understanding of the future fate of a cell with DNA damage. DNA damage is in principle repairable, or if extensive, can lead to cell death. Here, we have correlated the maximally induced DNA damage with three test substances in TK6 cells with the survival of the cells. For this, we selected hydrogen peroxide (H2O2) as an oxidizing agent, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 46 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…DNA damage caused by high glucose alone was not detectable using comet assay ( Fig. S1B ), as more than 20% DNA in the tail is recommended in the comet assay considering the recovery capacity of cells [ 27 ]. After H 2 O 2 treatment, the average tail moment under high glucose, which was higher than that of the control group, declined after FOXO1 knockdown ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DNA damage caused by high glucose alone was not detectable using comet assay ( Fig. S1B ), as more than 20% DNA in the tail is recommended in the comet assay considering the recovery capacity of cells [ 27 ]. After H 2 O 2 treatment, the average tail moment under high glucose, which was higher than that of the control group, declined after FOXO1 knockdown ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The genotoxicity tests were carried out to verify the effects of tested material on the genetic material of cells, which may affect their integrity 26 . Bankoglu et al reported that DNA damage above 20% negatively affected cell viability, therefore, for in vitro experiments where this level of damage was found, it is recommended to provide cell survival data in parallel 55 . Accordingly, to this recommendation, in the present study, despite many statistically significant differences between the sealants and the negative control, only BioRoot Flow and BioRoot RCS can be considered potentially genotoxic for the hGF cells after 48-h incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is an urgent imperative to actively pursue alternative therapeutic targets and novel, highly sensitive tumor biomarkers, with the aim of unveiling innovative treatment strategies. Sustained DNA damage in cells triggers repair pathways for cell survival, and the sort of DNA damage determines which repair pathways are activated [22]. Xray repair cross-complementing 1 (XRCC1), a vital DNA repair scaffold, interacts closely with DNA ligase IIIα (Lig-III) to orchestrate the mending of DNA singlestrand breaks triggered by ionizing radiation and alkylating agents, encompassing the base excision repair (BER) and single-strand break repair (SSBR) pathways [23,24].…”
Section: Introductionmentioning
confidence: 99%